OP0281 Recent Trends in Medication Usage for the Treatment of Juvenile Idiopathic Arthritis in the United States and the Influence of Tnf Inhibitors. (23rd January 2014) - Mannion, M.; Xie, F.; Curtis, J. R.; Beukelman, T.
Abstract : Background: The pharmacologic management of JIA has changed dramatically over the last decade with the advent of tumor necrosis factor inhibitors (TNFi), but the impact of TNFi on medication usage in routine clinical practice has not been well-studied. Objectives: Using national administrative claims from a large commercial U.S. health insurer, we investigated the use of medications in the treatment of JIA over the last 6 years. We examined medication use by calendar year, as well as medication use before and after new TNFi use among individual patients. Methods: Using data from January 2005 through September 2011, we identified children <17 years old with > 1 physician diagnosis code consistent with JIA. In the analyses of medication use by year, only subjects with full medical and pharmacy benefits for the entire calendar period were included. Use of TNFi, methotrexate (MTX), non-steroidal anti-inflammatory drugs (NSAIDs), and oral glucocorticoids (GC) was determined using outpatient pharmacy and infusion procedure claims. Significant changes in medication usage over time were evaluated with the Cochran-Armitage test for trend. New users of TNFi were defined by no receipt of any TNFi in the 6 months immediately prior to starting. New TNFi users were required to have a minimum of 6 months of follow-up after starting TNFi, and only the earliest episode of new TNFi use for each individual patient was included. Among prevalent users of NSAIDs and GC, we used paired t-tests to compare the number of filled prescriptions for NSAIDs and the cumulative mean daily GC dose (in prednisone equivalents) in the 6 months before and after new TNFi use. Results: Including all years of the study, we identified 3, 531 unique individuals with ≥1 JIA diagnosis code. Their median age was 11 years (IQR 7-14) and 64% were female. The proportion of patients receiving TNFi increased during the study period from 8.0% in 2005 to 21.9% in 2011 (p<0.0001). Over the same time period, the proportion of MTX users increased from 18.2% to 23.1% (p=0.02). The proportion of NSAIDs users (50.3% in 2005) and GC users (19.4% in 2005) was relatively unchanged over the study period (p=0.11 and p=0.10, respectively). We identified 269 new users of TNFi (72% etanercept, 17% adalimumab, 10% infliximab). Among 152 prevalent users of NSAIDs, the number of NSAID prescriptions decreased in the 6 months following new TNFi use (mean 2.89 prescriptions before versus 2.02 after; p<0.0001). Among 103 prevalent users of GC, the mean daily GC dose was significantly reduced in the 6 months following new TNFi use (mean decrease 3.1 mg/day; p=0.0002). Many new TNFi users (147/269; 55%) had not filled a prescription for MTX in the previous 6 months. Of these without recent MTX use, only 12% (17/147) used MTX in the 6 months following new TNFi use. Overall, 39% (105/269) had any concurrent MTX use in the 6 months following new TNFi use. Conclusions: TNFi use in the treatment of JIA has increased 2-3 fold over the last 6 years with a concurrent smaller increase in MTX use. New use of TNFi was associated with a reduction in the number of NSAID prescriptions and the mean daily GC dose. The relatively small proportion of patients with recent or concurrent use of MTX around the time of new TNFi use suggests that TNFi may be replacing, rather than complementing, MTX therapy in many patients. Disclosure of Interest: M. Mannion: None Declared, F. Xie: None Declared, J. Curtis Grant/research support from: Roche/Genentech, UCB, Janssen, Amgen, Pfizer, BMS, Crescendo, Merk, Lilly, CORRONA, Consultant for: Roche/Genentech, UCB, Janssen, Amgen, Pfizer, BMS, Crescendo, Merck, Lilly, CORRONA, AbbVie, T. Beukelman Grant/research support from: Pfizer, Consultant for: Novartis, Genentech/Roche